Charcoal from Coconut Shells: An Innovation in Agricultural Waste Management for Local Economic Development - Rahayu, Della Putri; Musthofa , M Arif; Dewi, Hasna; Kartika Devi, Erwina (CV. Civiliza Publishing, 2025)
Indonesia is one of the world's largest agrarian countries, with abundant agricultural and plantation outputs. Among its leading commodities, coconut holds a strategic role in both national and regional economies. However, the substantial volume of coconut shell waste is often underutilized. This study aims to explore the processing of coconut shell waste into high-value charcoal in Lagan Tengah Village and to analyze the production process, technical challenges, market potential, and its impact on community economic empowerment. Using a descriptive qualitative approach, data were collected through field observations, in-depth interviews, and documentation studies. The findings reveal that local business initiatives, such as “Jan Rahayu Lestari,” have succeeded in producing high-quality charcoal with a fixed carbon content of approximately 75%, low moisture levels, and long burn duration. The simple pyrolysis technology employed proves to be both effective and appropriate for the local community's capacity. This initiative not only generates alternative income for farmers and housewives but also mitigates environmental pollution caused by open burning. The study affirms that the integration of local knowledge with cross-sectoral support can transform agricultural waste management into a replicable, inclusive, and sustainable model for rural economic development. These findings are relevant for the formulation of policies related to green economy, renewable energy, and the strengthening of micro-industries based on local resources